2009
DOI: 10.3171/2008.9.jns08247
|View full text |Cite
|
Sign up to set email alerts
|

Memory outcome following transsylvian selective amygdalohippocampectomy in 62 patients with hippocampal sclerosis

Abstract: Results of the present study indicated that left-sided TSA for hippocampal sclerosis tends to improve verbal memory function with the preservation of other types of memory function. Moreover, right-sided TSA for hippocampal sclerosis can lead to significant improvement in memory function, with memory improvement observed 1 month after right-sided TSA and persisting 1 year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…13 However, in patients without these pathological changes, functions of the hippocampus are thought to remain to some degree, and postoperative memory losses were reported to be more severe. 9 In our study we retrospectively analyzed 37 patients who underwent transsylvian HT for the treatment of MTLE without hippocampal sclerosis or atrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 However, in patients without these pathological changes, functions of the hippocampus are thought to remain to some degree, and postoperative memory losses were reported to be more severe. 9 In our study we retrospectively analyzed 37 patients who underwent transsylvian HT for the treatment of MTLE without hippocampal sclerosis or atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…A standard frontotemporal craniotomy can be performed, but slightly wider exposure of the temporal lobe is necessary to permit intraoperative electrocorticography. 13 After wide exposure of the sylvian fissure, the inferior periinsular sulcus can be identified at the most inferior point of the insular gyri. Along this sulcus, the inferior horn of the lateral ventricle is opened with a cortical incision 15 mm in length (Fig.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…[16] In the study of Morino et al, a significant improvement in verbal memory tests was found after surgery in 62 unilateral HS patients who underwent selective amygdalohippocampectomy. [17] Another study on patients who had anterior temporal lobectomy, disclosed that visual memory tests (especially 'delayed recall') were improved significantly during the postoperative 6th and 12th months when compared with the preoperative results. There was no difference in verbal memory tests, however.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recurrent seizures might also result in deterioration of both verbal and spatial memory functions over time. Some reports show improvement in both verbal and spatial memory functions following SAH (1,24). Despite the risk of morbidity and mortality of surgery, epileptic seizures themselves have a higher risk, and surgical treatment has favorable and costeffective results in comparison with AEDs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas 90% of patients are diagnosed in developing countries, 40 to 70 per 100 million people are annually diagnosed in developed countries (1). Currently, surgical treatment has an important place in the management of epilepsy in accordance with the technical improvements in modern medicine, which leads to patients' quality of life improving (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%